PERANCANGAN GAME BERHITUNG UNTUK ANAK USIA 4-6 TAHUN PADA TK MUSLIMAT NU 09 PENANGGULAN KENDAL - Teguh Setiadi; Tegar Adi Putra (KH. A. Wahab Hasbullah University, 2018)
Early-age children live in the world of a play because that's needed a learning medium that is not only interactive but also interesting or more game. Age 4-6 years is a stage of age in an early age range (so-called pre-school age) in which the child is being prepared to enter a formal learning process. Expected in this age range, children have a more focused attitude of learning, not just playing, but began to recognize the learning process behind the game. The result of this research is that Game can be a tool in practicing arithmetic as well as with this game, children who follow numeracy lessons can practice counting by using existing computer facilities. The product of this research produced a medium or a means to introduce computer technology to children from an early age. Keyword: E-Learning, Multimedia, Game Education, Early-age children